SISTEM ADMINISTRASI KEPENDUDUKAN BERBASIS TEKNOLOGI INFORMASI (SAKTI) DALAM PELAYANAN ADMINISTRASI KEPENDUDUKAN DI KOTA KEDIRI PROVINSI JAWA TIMUR - Dedi Kusmana; Girisena Ergasera (Jurnal Media Birokrasi, 2019)
This study aims to find and analyze SAKTI program at the Department of Population and Civil Registration in the service of population administration based on online, barriers in the process of population administration services with SAKTI programs and efforts made by the Department of Population and Civil Registration of Kediri City. This program aims to facilitate the admin in finding population data and facilitate the community in the administration of population administration with online system related to Birth Certificate, Death, KTP-El and Child Identity Card (KIA). Based on the results of the analysis, SAKTI program contains a complete menu item content is easy to understand and help the community in obtaining the service of population administration quickly and easily. Implementation and various efforts undertaken by the Government of Kediri City Office of Population and Civil Registration Kediri in the implementation of the SAKTI program has been running very well based on the qualification of strategic issues concluded from the test litmus test on SWOT analysis but there are some obstacles that have not been in accordance with the target and target which is expected by the Government of Kediri City that is not yet fully optimal infrastructure, human resources are still lacking, the majority of people do not know the existence of SAKTI program, the socialization process is not optimal, the blind people of the internet can not operate the internet, the public assumption that the Kediri area is not too far in terms of distance to go to the Office of Population and Civil Registration. The Government's efforts include improving the socialization of 2018, distributing SAKTI guidebooks, BIMTEK (Technical Guidance), holding a "coffee tofu" meeting as an interactive program of government and community. Keywords: Information Technology, Administration, Population